Karakteristik batubara di Cekungan Bengkulu - Heryanto, Rachmat; Suyoko, Suyoko (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no4.20075Bengkulu Basin is known as a fore arc basin, which located in the southwestern part of Sumatera Island. Bengkulu Basin is occupied by Oligo-Miocene siliciclastic, coal, and carbonate sediments. Coal, one of alternative energies which can substitute hydrocarbon, is found within the sedimentary rocks of the Middle to Upper Miocene Lemau Formation as observed in Ketaun, Bengkulu, and Seluma areas. The thickness of the coal seams in the Ketaun area ranges from 100 to 200 cm, whereas in the Bengkulu area it varies between 100 to 350 cm, and in Seluma area up to 450 cm. Megascopically, coal seams in the Ketaun area are black in colour, dull to dull banded, with brownish black in streak, whereas in the Bengkulu and Seluma areas show a black colour, bright banded, and black streak. The mean of vitrinite reflectant value (Rv) of coal seam in the Ketaun area ranges from 0.41 to 0.49%, whereas in the Bengkulu and Seluma area it varies from 0.44 to 1.12%. The higher vitrinite reflectance of the Bengkulu and Seluma coals is probably due to the influence of andesitic sill intrusion. In general, the coal in the Ketaun area was deposited in an environment of relatively more to marine direction or limited influx clastic marsh or lower delta plain, where the tree density decreased. However, the coal in the Bengkulu and Seluma areas occurred in an environment which was relatively more to land direction or telmatic, or upper delta plain or wet forest swamp, where the tree density increased. Â